Management Strategy Risk For Support Transformation of the Surya Kencana Bogor Tourism Area - Cahyanti, Dina; Mbura, Helend A; Adhyatmoko, Nikolas Wisnu; Agung Wibawa, I Putu Satria; Muhardiansyah, Doni (Journal of Global Tourism, 2025)
Development area Surya Kencana tourism in harmony with The vision of the 2025–2045 Bogor City RPJPD is become a creative, advanced, and sustainable science city. This area own potential unique Because combine inheritance culture (heritage), tourism culinary typical local approach​ sustainability through green gastronomy, as well digital innovation by MSMEs. Approach thematic that integrates four target the give direction strategic in make Surya Kencana as destination tour featured based community. Research This identify eight risk main spread​ in three Category: security, safety, and comfort. Risks the covering low participation figure local, low awareness perpetrator culinary to sustainability, limitations infrastructure friendly environment, and not yet effectiveness utilization technology by MSMEs. Mitigation strategies risk done through involvement multi-stakeholder, education based community, improvement infrastructure, digitalization of MSMEs, and collaboration between government, society, and sectors private. Analysis results show that management risk No only tool technical, but become element strategic in build area resilient and empowered tourism​ competitiveness. Utilization digital technology, narrative culture local, and involvement community proven capable increase resilience area to disturbance physical, social, and environment. With approach this, Surya Kencana can contribute to development term length of Bogor City in sector inclusive and sustainable tourism